(meth)acrylic resin composition, inorganic microparticle dispersion slurry composition, and inorganic microparticle dispersed molded article
Patent Information
- Application Number
- CN202280012445.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-06-21
- Filing Date
- 2022-06-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-06-20
AI Technical Summary
[0014]然而,专利文献1中记载的聚乙烯醇缩醛树脂的分解温度高,存在无法应用于期望低温烧成的用途、例如无法用于使用容易氧化的铜等金属、低熔点玻璃等的用途的问题
[0266]根据本发明,可以提供在低温下具有优异的的分解性、并且能够提高无机微粒的分散性、凝聚抑制效果的(甲基)丙烯酸系树脂组合物。另外,可以提供使用该(甲基)丙烯酸系树脂组合物的无机微粒分散浆料组合物、无机微粒分散成形物。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0004365069260000041
Abstract
Description
Technical Field
[0001] This invention relates to (meth)acrylic resin compositions, inorganic microparticle dispersion slurry compositions, and inorganic microparticle dispersion molded articles. Background Technology
[0002] Compositions made by dispersing inorganic particles such as ceramic powder and glass particles in an adhesive resin are used in the production of laminated electronic components such as laminated ceramic capacitors.
[0003] Such multilayer ceramic capacitors are typically manufactured using the method described below. First, plasticizers, dispersants, and other additives are added to a solution made by dissolving adhesive resin in an organic solvent. Then, ceramic raw material powder is added, and the mixture is uniformly mixed using a ball mill or similar device to obtain an inorganic particulate dispersion slurry composition.
[0004] The inorganic microparticle dispersion slurry composition obtained is cast onto the surface of a support such as a polyethylene terephthalate film or SUS plate after demolding treatment using a doctor blade or a reverse roller coating machine. After the volatile components such as organic solvents are removed by distillation, the mixture is peeled off from the support to obtain a ceramic green sheet.
[0005] Next, a conductive paste for the internal electrodes is applied to the obtained ceramic green sheet using screen printing or similar methods. Multiple sheets are then stacked, heated, and pressed together to obtain a laminate. The laminate is then heated to undergo a degreasing process, where the binder resin and other components are thermally decomposed and removed. After firing, a sintered ceramic body with internal electrodes is obtained. Further, external electrodes are applied to the end faces of the sintered ceramic body, and it is fired again, thus completing the laminated ceramic capacitor.
[0006] In recent years, with the miniaturization of multilayer ceramic capacitors, the inorganic microparticles used have also been miniaturized. Miniaturized inorganic microparticles are prone to agglomeration in the paste. If agglomeration occurs, voids may remain during the degreasing and firing processes. Alternatively, the dispersibility of inorganic microparticles may decrease during the fabrication of multilayer ceramic capacitors, which in turn reduces the electrical properties of the product.
[0007] As adhesive resins, ethyl cellulose and polyvinyl acetal (PVB) resins are commonly used, for example. For instance, Patent Document 1 discloses a method for efficiently dispersing ceramic powder in a composition using these adhesives. Specifically, it discloses a method of first crushing ceramic powder such as calcium titanate in a solvent such as ethanol, and then adding resins such as polyvinyl butyral resin and ethyl cellulose resin.
[0008] In addition, Patent Document 2 discloses a method that uses acrylic resins and other materials as adhesives, in addition to polyvinyl butyral and cellulose polymers.
[0009] Existing technical documents
[0010] Patent documents
[0011] Patent Document 1: Japanese Patent Application Publication No. 2011-84433
[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-109761 Summary of the Invention
[0013] The problem that the invention aims to solve
[0014] However, the polyvinyl acetal resin described in Patent Document 1 has a high decomposition temperature, which makes it unsuitable for applications requiring low-temperature firing, such as applications using easily oxidized metals like copper or low-melting-point glass.
[0015] Furthermore, Patent Document 2 describes the use of an acrylic resin, but when using tiny inorganic particles with an average particle size of less than 1 μm, there is a problem of deteriorated dispersibility. In addition, the acrylic resin described in Patent Document 2 suffers from oxidation-induced degradation during degreasing, which requires high firing temperatures.
[0016] The object of this invention is to provide a (meth)acrylic resin composition that exhibits excellent decomposability at low temperatures and improves the dispersibility and agglomeration inhibition effect of inorganic particles. Furthermore, the object is to provide inorganic particle dispersion slurry compositions and inorganic particle dispersion molded articles using the (meth)acrylic resin composition.
[0017] means for solving problems
[0018] This application [1] relates to a (meth)acrylic resin composition containing a (meth)acrylic resin and an organic solvent, wherein the (meth)acrylic resin composition satisfies any one of (1) to (3) below, and the weight concentration of OH groups contained in the organic solvent is 9.0% by weight or more and 28.0% by weight or less.
[0019] (1) The above-mentioned (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (A) with a weight average molecular weight of 120,000 or more and 300,000 or less, and the weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (A) is 0.4% by weight or more and 2.0% by weight or less.
[0020] (2) The above-mentioned (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (B) with a weight average molecular weight of more than 300,000 and less than 500,000, and the weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (B) is more than 1.3% by weight and less than 3.5% by weight.
[0021] (3) The above-mentioned (meth)acrylic resin contains a low molecular weight (meth)acrylic resin (C) with a weight average molecular weight of 0.5 million or more and 100,000 or less, wherein the weight concentration of OH groups contained in the low molecular weight (meth)acrylic resin (C) is 1.3% by weight or more and 3.5% by weight or less, and the weight concentration of S atoms contained in the above-mentioned (meth)acrylic resin is 250 ppm or more and 20,000 ppm or less.
[0022] This application [2] relates to the (meth)acrylic resin composition of this application [1], which satisfies (1) and contains a low molecular weight (meth)acrylic resin with a weight average molecular weight of 0.5 million or more and 100,000 or less, wherein the weight concentration of OH groups contained in the low molecular weight (meth)acrylic resin is 1.3% by weight or more and 3.5% by weight or less, and the content of the low molecular weight (meth)acrylic resin is 0.1% by weight or more and 10% by weight or less relative to 100 parts by weight of high molecular weight (meth)acrylic resin (A).
[0023] This application [3] relates to the (meth)acrylic resin composition of this application [1], which satisfies (1) or (2), and the high molecular weight (meth)acrylic resin (A) or (B) has a solubility of 10 parts by weight or more in ethanol per 100 parts by weight of ethanol.
[0024] This application [4] relates to the (meth)acrylic resin composition of this application [1] or [3], which satisfies (1) or (2), and the high molecular weight (meth)acrylic resin (A) or (B) contains 79% by weight or more and 96% by weight of the structural unit represented by formula (a) and 3.1% by weight or more and 17% by weight of the structural unit represented by formula (b) relative to all structural units.
[0025] [Chemical Formula 1]
[0026]
[0027] In equation (a), R 1 In formula (b), R represents a straight-chain or branched alkyl group having 1 to 8 carbon atoms. 2 It refers to a straight-chain or branched alkyl group in which at least one of the hydrogen atoms is replaced by an OH group, and the number of carbon atoms is 2 to 4.
[0028] This application [5] relates to a (meth)acrylic resin composition of this application [1], [3] or [4], which satisfies (1) or (2) and the weight concentration of OH groups contained in the organic solvent relative to the weight concentration of OH groups contained in the high molecular weight (meth)acrylic resin (A) or (B) (weight concentration of OH groups contained in the organic solvent / weight concentration of OH groups contained in the high molecular weight (meth)acrylic resin (A) or (B)) is 4.5 or more and 46.2 or less.
[0029] This application [6] relates to a (meth)acrylic resin composition of this application [1], [3], [4] or [5], which satisfies (2) and the (meth)acrylic resin is composed only of a high molecular weight (meth)acrylic resin (B), wherein the weight concentration of S atoms contained in the (meth)acrylic resin is 250 ppm or more and 20,000 ppm or less.
[0030] This application [7] relates to an inorganic microparticle dispersion slurry composition containing any one of the (meth)acrylic resin compositions, inorganic microparticles and plasticizers described in any one of the applications [1] to [6].
[0031] This application [8] relates to an inorganic microparticle dispersion molding article, which is made using the inorganic microparticle dispersion slurry composition of this application [7].
[0032] The present invention will now be described in detail.
[0033] The inventors have discovered that by combining a (meth)acrylic resin having a specified weight-average molecular weight, weight concentration of OH groups, and weight concentration of S atoms with an organic solvent having a weight concentration of OH groups of 9.0% to 28.0% by weight, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and agglomeration inhibition effect of inorganic particles, thus completing the present invention.
[0034] The (meth)acrylic resin composition of the present invention contains (meth)acrylic resin.
[0035] The above-mentioned (meth)acrylic resin satisfies any one of (1) to (3) below.
[0036] (1) The above-mentioned (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (A) with a weight average molecular weight of 120,000 or more and 300,000 or less, and the weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (A) is 0.4% by weight or more and 2.0% by weight or less.
[0037] (2) The above-mentioned (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (B) with a weight average molecular weight of more than 300,000 and less than 500,000, and the weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (B) is more than 1.3% by weight and less than 3.5% by weight.
[0038] (3) The above-mentioned (meth)acrylic resin contains a low molecular weight (meth)acrylic resin (C) with a weight average molecular weight of 0.5 million or more and 100,000 or less, wherein the weight concentration of OH groups contained in the low molecular weight (meth)acrylic resin is 1.3% by weight or more and 3.5% by weight or less, and the weight concentration of S atoms contained in the (meth)acrylic resin is 250 ppm or more and 20,000 ppm or less. By satisfying the above-mentioned configuration, the dispersibility of inorganic microparticles can be sufficiently improved when preparing an inorganic microparticle dispersion slurry composition. In addition, the aggregation of inorganic microparticles can be suppressed.
[0039] <High molecular weight (meth)acrylic resin (A)>
[0040] In the (meth)acrylic resin composition of the present invention that satisfies (1) above, the (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (A).
[0041] The weight-average molecular weight of the aforementioned high molecular weight (meth)acrylic resin (A) is above 120,000 and below 300,000.
[0042] By setting the parameters within the aforementioned range, the dispersibility of inorganic microparticles can be sufficiently improved when preparing inorganic microparticle dispersion slurry compositions. Furthermore, the aggregation of inorganic microparticles can be suppressed.
[0043] The weight-average molecular weight is preferably 150,000 or more, more preferably 180,000 or more, preferably 250,000 or less, and more preferably 220,000 or less.
[0044] By setting the viscosity within the range described above, the inorganic microparticle dispersion slurry composition achieves sufficient viscosity and improves printability.
[0045] Furthermore, the ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the above-mentioned high molecular weight (meth)acrylic resin (A) is preferably 2 or more, and more preferably 8 or less.
[0046] By setting the viscosity within the aforementioned range, the inorganic microparticle dispersion slurry composition exhibits a preferred viscosity due to its moderately low degree of polymerization, thereby improving productivity. Furthermore, the resulting inorganic microparticle dispersion sheets possess adequate sheet strength. Additionally, the surface smoothness of the obtained ceramic green sheets can be significantly improved.
[0047] The Mw / Mn ratio is more preferably 3 or more, and more preferably 6 or less.
[0048] It should be noted that the weight-average molecular weight (Mw) and number-average molecular weight (Mn) are average molecular weights converted from polystyrene and can be obtained by GPC determination using, for example, a column LF-804 (manufactured by Showa Denko).
[0049] The weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (A) is 0.4% by weight or more and 2.0% by weight or less.
[0050] By setting the parameters within the aforementioned range, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0051] The weight concentration of the OH group is preferably 0.5% by weight or more, more preferably 0.6% by weight or more, preferably 1.6% by weight or less, and more preferably 1.4% by weight or less.
[0052] The weight concentration of the OH groups mentioned above refers to the ratio of the weight of the OH groups to the total weight of the high molecular weight (meth)acrylic resin (A), which can be calculated based on the following formula.
[0053] The weight concentration of OH groups in high molecular weight (meth)acrylic resin (A) = [weight of OH groups in all monomers / (weight of all monomers + weight of polymerization initiator)] × 100
[0054] <High molecular weight (meth)acrylic resin (B)>
[0055] In the (meth)acrylic resin composition of the present invention that satisfies (2) above, the (meth)acrylic resin contains a high molecular weight (meth)acrylic resin (B).
[0056] The weight-average molecular weight of the aforementioned high molecular weight (meth)acrylic resin (A) exceeds 300,000 but is less than 500,000.
[0057] By setting the parameters within the aforementioned range, the dispersibility of inorganic microparticles can be sufficiently improved when preparing inorganic microparticle dispersion slurry compositions. Furthermore, the aggregation of inorganic microparticles can be suppressed.
[0058] The weight-average molecular weight is preferably 320,000 or more, more preferably 330,000 or more, preferably 480,000 or less, and more preferably 450,000 or less.
[0059] By setting it to the above range, sufficient viscosity is achieved when preparing inorganic microparticle dispersion slurry compositions, and printability is also improved.
[0060] Furthermore, the ratio (Mw / Mn) of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the above-mentioned high molecular weight (meth)acrylic resin (B) is preferably 2 or more, and more preferably 8 or less.
[0061] By setting the viscosity within the aforementioned range, the inorganic microparticle dispersion slurry composition exhibits a preferred viscosity due to the moderate presence of components with low polymerization degree, thereby improving productivity. Furthermore, the resulting inorganic microparticle dispersion sheets possess adequate sheet strength. Additionally, the surface smoothness of the obtained ceramic green sheets can be significantly improved.
[0062] The Mw / Mn ratio is more preferably 3 or more, and more preferably 6 or less.
[0063] The weight concentration of OH groups contained in the above-mentioned high molecular weight (meth)acrylic resin (B) is 1.3% by weight or more and 3.5% by weight or less.
[0064] By setting the parameters within the aforementioned range, the adhesive resin can exhibit excellent decomposability even at low temperatures, and it can also improve the dispersibility of inorganic particles and the aggregation inhibition effect.
[0065] The weight concentration of the OH group is preferably 1.5% by weight or more, more preferably 2% by weight or more, more preferably 3.3% by weight or less, more preferably 3% by weight or less.
[0066] The weight concentration of the OH groups mentioned above refers to the ratio of the weight of the OH groups to the total weight of the high molecular weight (meth)acrylic resin (B), which can be calculated based on the following formula.
[0067] The weight concentration of OH groups in high molecular weight (meth)acrylic resin (B) = [weight of OH groups in all monomers / (weight of all monomers + weight of polymerization initiator)] × 100
[0068] The above-mentioned high molecular weight (meth)acrylic resins (A) and (B) preferably have structural units represented by the following formula (a), and more preferably have structural units represented by the following formula (b).
[0069] [Chemical Formula 2]
[0070]
[0071] In equation (a), R 1 In formula (b), R represents a straight-chain or branched alkyl group having 1 to 8 carbon atoms. 2 It refers to a straight-chain or branched alkyl group in which at least one of the hydrogen atoms is replaced by an OH group, and the number of carbon atoms is 2 to 4.
[0072] As mentioned above, R 1More preferably, it is a straight-chain or branched alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, etc.
[0073] As mentioned above, R 2 Preferably, it is a straight-chain or branched alkyl group with 2 to 4 carbon atoms in which at least one of the hydrogen atoms is replaced by an OH group, for example: 2-hydroxyethyl, 2-hydroxypropyl, 2-hydroxybutyl, etc.
[0074] The content of the structural unit represented by formula (a) in the above-mentioned high molecular weight (meth)acrylic resins (A) and (B) is preferably 79% by weight or more, and preferably 96% by weight or less.
[0075] By setting it to the above range, low-temperature decomposition can be significantly improved.
[0076] The content of the structural unit represented by the above formula (a) is more preferably 85% by weight or more, and more preferably 95% by weight or less.
[0077] The content of the structural unit represented by formula (b) in the above-mentioned high molecular weight (meth)acrylic resins (A) and (B) is preferably 3.1% by weight or more, and preferably 17% by weight or less.
[0078] Ethanol is often used as a solvent for adhesive resins. However, acrylic resins generally have lower solubility in ethanol compared to polyvinyl acetal resins. If acrylic resin is added after the initial crushing, there is a problem of inorganic particle aggregation. However, by setting it within the above range, the dispersibility of inorganic particles and the aggregation inhibition effect can be improved.
[0079] In addition, it can further improve solubility in ethanol.
[0080] The content of the structural unit represented by the above formula (2) is more preferably 4% by weight or more, and more preferably 15% by weight or less.
[0081] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) preferably have segments derived from (meth)acrylic esters with straight or branched alkyl groups having 3 to 4 carbon atoms.
[0082] By incorporating the aforementioned chain segments, the low-temperature decomposability can be improved.
[0083] Examples of (meth)acrylates having 3 to 4 carbon atoms and being either straight-chain or branched alkyl groups include: n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate. Isobutyl (meth)acrylate is preferred.
[0084] In the above-mentioned high molecular weight (meth)acrylic resins (A) and (B), the content of segments derived from (meth)acrylic esters having 3 to 4 carbon atoms in straight-chain or branched alkyl groups is preferably 30% by weight or more, more preferably 40% by weight or more, preferably 95% by weight or less, more preferably 88% by weight or less.
[0085] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) may have segments derived from (meth)acrylic esters having alkyl groups having 1 to 2 carbon atoms.
[0086] Examples of (meth)acrylates having 1 to 2 carbon atoms include methyl (meth)acrylate and ethyl (meth)acrylate.
[0087] In the above-mentioned high molecular weight (meth)acrylic resins (A) and (B), the content of segments derived from (meth)acrylic esters having 1 to 2 carbon atoms is preferably 0% by weight or more, more preferably 10% by weight or more, preferably 66.8% by weight or less, more preferably 46% by weight or less.
[0088] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) may have segments of (meth)acrylic esters derived from straight-chain or branched alkyl groups having 5 to 8 carbon atoms.
[0089] Examples of (meth)acrylates having a straight-chain or branched alkyl group having 5 to 8 carbon atoms include n-amyl (meth)acrylate, isoamyl (meth)acrylate, neoamyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, (meth)acrylates having a straight-chain or branched alkyl group having 6 to 8 carbon atoms are preferred, and 2-ethylhexyl (meth)acrylate is more preferred.
[0090] In the above-mentioned high molecular weight (meth)acrylic resins (A) and (B), the content of (meth)acrylic ester segments derived from straight-chain or branched alkyl groups having 5 to 8 carbon atoms is preferably 0% by weight or more, more preferably 9% by weight or more, preferably 25% by weight or less, more preferably 20% by weight or less.
[0091] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) may have segments of (meth)acrylic esters derived from straight-chain or branched alkyl groups having nine or more carbon atoms.
[0092] Examples of (meth)acrylates having a straight-chain or branched alkyl group having 9 or more carbon atoms include: n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, lauryl methacrylate, isolauryl methacrylate, stearyl methacrylate, isostearyl methacrylate, etc.
[0093] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) preferably have segments of (meth)acrylic esters derived from straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group.
[0094] By possessing the aforementioned chain segments, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0095] As a linear or branched alkyl group having at least one hydrogen atom substituted with an OH group, the preferred (meth)acrylate is a (meth)acrylate having an OH group weight ratio of 10.5% or more, more preferably an (meth)acrylate having an OH group weight ratio of 11.5% or more, and more preferably an (meth)acrylate having an OH group weight ratio of 13.1% or less.
[0096] The above-mentioned high molecular weight (meth)acrylic resins (A) and (B) preferably have segments of (meth)acrylic esters consisting of 2 to 4 straight-chain or branched alkyl groups having at least one carbon atom substituted with an OH group among the hydrogen atoms.
[0097] Examples of (meth)acrylates having at least one hydrogen atom substituted with an OH group and comprising 2 to 4 straight-chain or branched alkyl groups include, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate are preferred.
[0098] In the above-mentioned high molecular weight (meth)acrylic resins (A) and (B), the content of (meth)acrylate segments having at least one carbon atom substituted by an OH group and having 2 to 4 straight-chain or branched alkyl groups is preferably 3.1% by weight or more, more preferably 5.0% by weight or more, preferably 17.0% by weight or less, more preferably 12.2% by weight or less.
[0099] The aforementioned high molecular weight (meth)acrylic resins (A) and (B) preferably have segments of (meth)acrylic esters comprising at least 5 or more straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group.
[0100] Examples of (meth)acrylates that are straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group and having 5 or more carbon atoms include: hydroxypentyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyheptyl (meth)acrylate, hydroxyoctyl (meth)acrylate, etc.
[0101] In addition to segments derived from the aforementioned (meth)acrylates, the aforementioned high molecular weight (meth)acrylate resins (A) and (B) may also have segments derived from (meth)acrylates, segments derived from other (meth)acrylates such as (meth)acrylates with glycidyl groups.
[0102] The glass transition temperature (Tg) of the above-mentioned high molecular weight (meth)acrylic resins (A) and (B) is preferably 30°C or higher and 85°C or lower.
[0103] By setting it to the above range, the amount of plasticizer added can be reduced, and low-temperature decomposition resistance can be improved.
[0104] The above-mentioned Tg is more preferably 32°C or above, further preferably 42°C or above, even more preferably 45°C or above, particularly preferably 50°C or above, more preferably 80°C or below, and even more preferably 75°C or below.
[0105] It should be noted that the glass transition temperature (Tg) mentioned above can be measured, for example, using a differential scanning calorimeter (DSC).
[0106] The solubility of the above-mentioned high molecular weight (meth)acrylic resins (A) and (B) in ethanol is preferably 10 parts by weight or more per 100 parts by weight of ethanol.
[0107] By setting the parameters within the aforementioned range, the dispersibility of inorganic particles and the effect of inhibiting aggregation can be improved. Furthermore, the solubility in organic solvents can be significantly increased.
[0108] The solubility in ethanol is more preferably 50 parts by weight or more, and even more preferably 100 parts by weight or more.
[0109] The solubility in ethanol mentioned above refers to the amount of resin required to dissolve 100 parts by weight of ethanol at 25°C until a precipitate is formed.
[0110] The content of the above-mentioned high molecular weight (meth)acrylic resin (A) in the (meth)acrylic resin composition of the present invention is preferably 5% by weight or more, more preferably 10% by weight or more, further preferably 30% by weight or more, preferably 70% by weight or less, and more preferably 60% by weight or less.
[0111] The content of the above-mentioned high molecular weight (meth)acrylic resin (B) in the (meth)acrylic resin composition of the present invention is preferably 5% by weight or more, more preferably 10% by weight or more, further preferably 30% by weight or more, preferably 70% by weight or less, and more preferably 60% by weight or less.
[0112] Furthermore, in the (meth)acrylic resin composition of the present invention that satisfies (2) above, the weight concentration of S atoms contained in the (meth)acrylic resin is preferably 250 ppm or more, and preferably 20,000 ppm or less.
[0113] By setting the parameters within the aforementioned range, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0114] The weight concentration of S atoms is more preferably 400 ppm or more, and more preferably 15,000 ppm or less.
[0115] The weight concentration of S atoms mentioned above refers to the ratio of the weight of S atoms to the weight of (meth)acrylic resin, which can be calculated based on the following formula.
[0116] The weight concentration of sulfur atoms in (meth)acrylic resins = [weight of sulfur atoms in the chain transfer agent / (weight of all monomers + weight of polymerization initiator + weight of chain transfer agent)] × 100
[0117] It should be noted that when the above-mentioned (meth)acrylic resin composition contains multiple (meth)acrylic resins, the weight concentration of the S atoms can be calculated based on the weight concentration of S atoms contained in each (meth)acrylic resin and the proportion of each (meth)acrylic resin.
[0118] In addition, the weight concentration of S atoms mentioned above can also be determined by ICP-AES (inductively coupled plasma optical emission spectrometry).
[0119] The methods for manufacturing the above-mentioned high molecular weight (meth)acrylic resins (A) and (B) are not particularly limited. For example, one method is to add an organic solvent or the like to a mixture of raw material monomers including (meth)acrylates to prepare a monomer mixture, and then add a polymerization initiator and a chain transfer agent to the obtained monomer mixture to copolymerize the above-mentioned raw material monomers.
[0120] There are no particular limitations on the polymerization method, and examples include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, and solution polymerization. Among these, solution polymerization is preferred.
[0121] Examples of polymerization initiators include: tert-butyl peroxypentanoate, p-menthol peroxide, diisopropylbenzene peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropylbenzene peroxide, tert-butyl hydroperoxide, cyclohexanone peroxide, and bisuccinic acid peroxide.
[0122] Examples of chain transfer agents mentioned above include: 3-mercapto-1,2-propanediol, 3-mercapto-1-propanol, 3-mercapto-2-butanol, 8-mercapto-1-octanol, mercaptosuccinic acid, and mercaptoacetic acid.
[0123] <Low molecular weight (meth)acrylic resin (C)>
[0124] In the (meth)acrylic resin composition of the present invention that satisfies (3) above, the (meth)acrylic resin contains a low molecular weight (meth)acrylic resin (C).
[0125] In this specification, the weight-average molecular weight of the aforementioned low molecular weight (meth)acrylic resin (C) is 0.5 million or more and 100,000 or less.
[0126] By containing the aforementioned low molecular weight (meth)acrylic resin (C), the dispersibility of inorganic particles can be improved.
[0127] The aforementioned weight-average molecular weight is more preferably 0.6 million or more, even more preferably 0.8 million or more, more preferably 90,000 or less, and even more preferably 30,000 or less.
[0128] Furthermore, the weight-average molecular weight (Mw) to number-average molecular weight (Mn) ratio (Mw / Mn) of the aforementioned low molecular weight (meth)acrylic resin (C) is preferably 1.3 or more, more preferably 2 or more, and more preferably 8 or less.
[0129] By setting the viscosity within the aforementioned range, the inorganic microparticle dispersion slurry composition exhibits a preferred viscosity due to its moderately low degree of polymerization, thereby improving productivity. Furthermore, the resulting inorganic microparticle dispersion sheets possess moderate sheet strength. Additionally, the surface smoothness of the obtained ceramic green sheets can be significantly improved.
[0130] The Mw / Mn ratio is more preferably 3 or more, and more preferably 6 or less.
[0131] It should be noted that the weight-average molecular weight (Mw) and number-average molecular weight (Mn) are average molecular weights converted from polystyrene and can be obtained by GPC determination using, for example, a column LF-804 (manufactured by Showa Denko).
[0132] The weight concentration of OH groups contained in the above-mentioned low molecular weight (meth)acrylic resin (C) is 1.3% by weight or more and 3.5% by weight or less.
[0133] By setting the parameters within the aforementioned range, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0134] The weight concentration of the OH group is preferably 1.4% by weight or more, preferably 3.3% by weight or less, and more preferably 3.2% by weight or less.
[0135] The weight concentration of the OH groups mentioned above refers to the ratio of the weight of the OH groups to the total weight of the low molecular weight (meth)acrylic resin (C), which can be calculated based on the following formula.
[0136] The weight concentration of OH groups in low molecular weight (meth)acrylic resin (C) = [(Weight of OH groups in all monomers + Weight of OH groups in chain transfer agent) / (Weight of all monomers + Weight of polymerization initiator + Weight of chain transfer agent)] × 100
[0137] The aforementioned low molecular weight (meth)acrylic resin (C) preferably has segments derived from (meth)acrylic esters with straight or branched alkyl groups having 3 to 4 carbon atoms.
[0138] By incorporating the aforementioned chain segments, the low-temperature decomposability can be improved.
[0139] Examples of (meth)acrylates having 3 to 4 carbon atoms and being either straight-chain or branched alkyl groups include: n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate. Isobutyl (meth)acrylate is preferred.
[0140] In the above-mentioned low molecular weight (meth)acrylic resin (C), the content of (meth)acrylic ester segments having 3 to 4 carbon atoms is preferably 38% by weight or more, more preferably 50% by weight or more, more preferably 80% by weight or less, and more preferably 75% by weight or less.
[0141] The aforementioned low molecular weight (meth)acrylic resin (C) may have segments derived from (meth)acrylic esters having alkyl groups having 1 to 2 carbon atoms.
[0142] Examples of (meth)acrylates having 1 to 2 carbon atoms include methyl (meth)acrylate and ethyl (meth)acrylate.
[0143] In the above-mentioned low molecular weight (meth)acrylic resin (C), the content of segments derived from (meth)acrylic esters having 1 to 2 carbon atoms is preferably 0% by weight or more, more preferably 7% by weight or more, preferably 33% by weight or less, more preferably 20.5% by weight or less.
[0144] The aforementioned low molecular weight (meth)acrylic resin (C) may have segments of (meth)acrylic esters derived from straight-chain or branched alkyl groups having 5 to 8 carbon atoms.
[0145] Examples of (meth)acrylates having a straight-chain or branched alkyl group having 5 to 8 carbon atoms include n-amyl (meth)acrylate, isoamyl (meth)acrylate, neoamyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, (meth)acrylates having a straight-chain or branched alkyl group having 6 to 8 carbon atoms are preferred, and 2-ethylhexyl (meth)acrylate is more preferred.
[0146] In the above-mentioned low molecular weight (meth)acrylic resin (C), the content of (meth)acrylate segments from straight-chain or branched alkyl groups having 5 to 8 carbon atoms is preferably 0% by weight or more, more preferably 10% by weight or more, more preferably 40% by weight or less, and more preferably 30% by weight or less.
[0147] The aforementioned low molecular weight (meth)acrylic resin (C) may have segments of (meth)acrylic esters derived from straight-chain or branched alkyl groups having nine or more carbon atoms.
[0148] Examples of (meth)acrylates having a straight-chain or branched alkyl group having 9 or more carbon atoms include: n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, lauryl methacrylate, isolauryl methacrylate, stearyl methacrylate, isostearyl methacrylate, etc.
[0149] The aforementioned low molecular weight (meth)acrylic resin (C) preferably has segments of (meth)acrylate derived from straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group.
[0150] By possessing the aforementioned chain segments, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0151] As a linear or branched alkyl group having at least one hydrogen atom substituted with an OH group, the preferred (meth)acrylate is a (meth)acrylate having an OH group weight ratio of 10.5% or more, more preferably an (meth)acrylate having an OH group weight ratio of 11.5% or more, and more preferably an (meth)acrylate having an OH group weight ratio of 13.1% or less.
[0152] The aforementioned low molecular weight (meth)acrylic resin (C) preferably has segments of (meth)acrylate derived from a straight-chain or branched alkyl group having at least one hydrogen atom substituted with an OH group and having 2 to 4 carbon atoms.
[0153] Examples of (meth)acrylates having at least one hydrogen atom substituted with an OH group and comprising 2 to 4 straight-chain or branched alkyl groups include, for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate are preferred.
[0154] In the above-mentioned low molecular weight (meth)acrylic resin (C), the content of (meth)acrylate segments having at least one carbon atom substituted by an OH group in the hydrogen atom and having 2 to 4 straight-chain or branched alkyl groups is preferably 7% by weight or more, more preferably 10% by weight or more, preferably 20% by weight or less, more preferably 16% by weight or less.
[0155] The aforementioned low molecular weight (meth)acrylic resin (C) preferably has segments of (meth)acrylic esters comprising at least 5 or more straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group.
[0156] Examples of (meth)acrylates that are straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group and having 5 or more carbon atoms include: hydroxypentyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyheptyl (meth)acrylate, hydroxyoctyl (meth)acrylate, etc.
[0157] In addition to segments derived from the aforementioned (meth)acrylates, the aforementioned low molecular weight (meth)acrylate resin (C) may also have segments derived from (meth)acrylates, segments derived from other (meth)acrylates such as (meth)acrylates with glycidyl groups.
[0158] In addition, in the (meth)acrylic resin composition of the present invention that satisfies (3) above, the weight concentration of S atoms contained in the (meth)acrylic resin is 250 ppm or more and 20,000 ppm or less.
[0159] By setting the parameters within the aforementioned range, the adhesive resin can exhibit excellent decomposability even at low temperatures, and can also improve the dispersibility and aggregation inhibition effect of inorganic particles.
[0160] The weight concentration of the S atoms is preferably 1500 ppm or more, more preferably 3000 ppm or more, more preferably 18000 ppm or less, and more preferably 10000 ppm or less.
[0161] The weight concentration of S atoms mentioned above refers to the ratio of the weight of S atoms to the weight of (meth)acrylic resin, which can be calculated based on the following formula.
[0162] The weight concentration of sulfur atoms in (meth)acrylic resins = [weight of sulfur atoms in the chain transfer agent / (weight of all monomers + weight of polymerization initiator + weight of chain transfer agent)] × 100
[0163] It should be noted that when the above-mentioned (meth)acrylic resin composition contains multiple (meth)acrylic resins, the weight concentration of the S atoms can be calculated based on the weight concentration of S atoms contained in each (meth)acrylic resin and the proportion of each (meth)acrylic resin.
[0164] In addition, the weight concentration of S atoms mentioned above can also be determined by ICP-AES (inductively coupled plasma optical emission spectrometry).
[0165] The glass transition temperature (Tg) of the above-mentioned low molecular weight (meth)acrylic resin (C) is above 30°C and below 60°C.
[0166] By setting it to the above range, the amount of plasticizer added can be reduced, and low-temperature decomposition resistance can be improved.
[0167] The above-mentioned Tg is preferably 32°C or higher, more preferably 42°C or higher, even more preferably 45°C or higher, preferably 58°C or lower, and more preferably 50°C or lower.
[0168] It should be noted that the glass transition temperature (Tg) mentioned above can be measured, for example, using a differential scanning calorimeter (DSC).
[0169] In the (meth)acrylic resin composition of the present invention, the content of the low molecular weight (meth)acrylic resin (C) is preferably 0.006% by weight or more, more preferably 0.01% by weight or more, preferably 10% by weight or less, more preferably 8% by weight or less.
[0170] In addition, in the (meth)acrylic resin composition of the present invention that satisfies (1) above, it is preferable that, in addition to the above-mentioned high molecular weight (meth)acrylic resin (A), the above-mentioned (meth)acrylic resin also contains the above-mentioned low molecular weight (meth)acrylic resin (B).
[0171] Furthermore, by including the aforementioned low molecular weight (meth)acrylic resin (C), the dispersibility of inorganic particles can be further improved.
[0172] In the (meth)acrylic resin composition of the present invention that satisfies (1) above, the content of the low molecular weight (meth)acrylic resin (C) is preferably 0.1 parts by weight or more, and preferably 10 parts by weight or less, relative to 100 parts by weight of the high molecular weight (meth)acrylic resin (A).
[0173] By setting the range described above, the dispersibility of inorganic particles can be further improved.
[0174] The content of low molecular weight (meth)acrylic resin (C) is more preferably 0.3 parts by weight or more, and more preferably 7.5 parts by weight or less, relative to 100 parts by weight of the high molecular weight (meth)acrylic resin.
[0175] There are no particular limitations on the method for manufacturing the aforementioned low molecular weight (meth)acrylic resin (C). For example, one method may be to prepare a monomer mixture by adding an organic solvent to a mixture of raw material monomers including (meth)acrylates, and then further adding a polymerization initiator and a chain transfer agent to the obtained monomer mixture to copolymerize the aforementioned raw material monomers.
[0176] There are no particular limitations on the polymerization method, and examples include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, and solution polymerization. Among these, solution polymerization is preferred.
[0177] Examples of polymerization initiators include: tert-butyl peroxypentanoate, p-menthol peroxide, diisopropylbenzene peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, isopropylbenzene peroxide, tert-butyl hydroperoxide, cyclohexanone peroxide, and bisuccinic acid peroxide.
[0178] Examples of chain transfer agents mentioned above include: 3-mercapto-1,2-propanediol, 3-mercapto-1-propanol, 3-mercapto-2-butanol, 8-mercapto-1-octanol, mercaptosuccinic acid, and mercaptoacetic acid.
[0179] <Organic Solvents>
[0180] The (meth)acrylic resin composition of the present invention contains an organic solvent.
[0181] The weight concentration of OH groups contained in the above organic solvent is 9.0% by weight or more and 28.0% by weight or less.
[0182] By incorporating the aforementioned organic solvents, the dispersibility of inorganic particles and the effect of inhibiting aggregation can be improved.
[0183] The weight concentration of the OH group is preferably 11.0% by weight or more, more preferably 13.0% by weight or more, preferably 26.0% by weight or less, more preferably 24% by weight or less, and even more preferably 22.5% by weight or less.
[0184] The weight concentration of the OH groups mentioned above refers to the ratio of the weight of the OH groups to the total weight of the organic solvent, which can be calculated based on the following formula.
[0185] The weight concentration of OH groups in an organic solvent = (weight of OH groups in the total organic solvent / weight of the total organic solvent) × 100
[0186] The weight concentration of OH groups contained in the organic solvent relative to the weight concentration of OH groups contained in the high molecular weight (meth)acrylic resins (A) and (B) (weight concentration of OH groups in the organic solvent / weight concentration of OH groups in the high molecular weight (meth)acrylic resin) is preferably 4.5 or more, and preferably 46.2 or less.
[0187] By setting the range as described above, the dispersibility and aggregation inhibition effect of inorganic particles can be further improved.
[0188] The above ratio is more preferably 8.1 or more, further preferably 10 or more, more preferably 40 or less, further preferably 30 or less, even more preferably 25 or less, and particularly preferably 20 or less.
[0189] The above-mentioned organic solvents include organic solvents with OH groups.
[0190] Examples of organic solvents containing OH groups include aliphatic alcohols, cyclic alcohols, and alicyclic alcohols.
[0191] Examples of the aforementioned aliphatic alcohols include: ethanol, propanol, isopropanol, heptanol, octanol, decanol, tridecanol, lauryl alcohol, tetradecanol, cetyl alcohol, 2-ethyl-1-hexanol, octadecanol, hexadecenol, oleyl alcohol, TEXANOL, 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, etc.
[0192] Examples of the aforementioned cyclic alcohols include cresol and eugenol.
[0193] Examples of the aforementioned alicyclic alcohols include cycloalkanols such as cyclohexanol, terpineols, dihydroterpineols, and other terpenoid alcohols.
[0194] Among them, aliphatic alcohols are preferred, and ethanol, isopropanol, 2-butyl-2-ethyl-1,3-propanediol, neopentyl glycol, and TEXANOL are also preferred.
[0195] The molecular weight of the organic solvent having an OH group is preferably 46 or more, more preferably 60 or more, preferably 220 or less, and more preferably 160 or less.
[0196] Furthermore, the number of carbon atoms in the aforementioned organic solvents containing OH groups is preferably 2 or more, more preferably 3 or more, more preferably 12 or less, and more preferably 10 or less.
[0197] The weight percentage of OH groups contained in the above-mentioned organic solvents containing OH groups is preferably 7.5% by weight or more, more preferably 15% by weight or more, even more preferably 21% by weight or more, and preferably 37% by weight or less.
[0198] The content of the organic solvent having an OH group relative to the total content of the above-mentioned organic solvent is preferably 29% by weight or more, more preferably 43% by weight or more, preferably 79% by weight or less, more preferably 61% by weight or less.
[0199] The aforementioned organic solvents may contain other organic solvents besides those with OH groups.
[0200] Other organic solvents mentioned above include, for example, ketones such as acetone, methyl ethyl ketone, diacetone, and diisobutyl ketone; aromatic hydrocarbons such as toluene and xylene; and esters such as methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, butyl butyrate, methyl valerate, ethyl valerate, butyl valerate, methyl hexanoate, ethyl hexanoate, butyl hexanoate, ethyl acetate, butyl acetate, 2-ethylhexyl acetate, and 2-ethylhexyl butyrate.
[0201] Among them, toluene, butyl acetate, and methyl ethyl ketone are preferred.
[0202] The content of the other organic solvents mentioned above relative to the total content of the organic solvents is preferably 21% by weight or more, more preferably 39% by weight or more, preferably 71% by weight or less, and more preferably 57% by weight or less.
[0203] The content of the above-mentioned organic solvent in the (meth)acrylic resin composition of the present invention is preferably 20% by weight or more, more preferably 30% by weight or more, preferably 95% by weight or less, more preferably 70% by weight or less, and even more preferably 60% by weight or less.
[0204] Relative to 100 parts by weight of the above-mentioned (meth)acrylic resin, the content of the above-mentioned organic solvent in the (meth)acrylic resin composition of the present invention is preferably 25 parts by weight or more, more preferably 100 parts by weight or more, preferably 2000 parts by weight or less, and more preferably 1500 parts by weight or less.
[0205] Relative to 100 parts by weight of the above-mentioned high molecular weight (meth)acrylic resin (A), the content of the above-mentioned organic solvent in the (meth)acrylic resin composition of the present invention is preferably 25 parts by weight or more, more preferably 42.9 parts by weight or more, preferably 1900 parts by weight or less, more preferably 233.3 parts by weight or less, and more preferably 150 parts by weight or less.
[0206] Relative to 100 parts by weight of the above-mentioned high molecular weight (meth)acrylic resin (B), the content of the above-mentioned organic solvent in the (meth)acrylic resin composition of the present invention is preferably 25 parts by weight or more, more preferably 100 parts by weight or more, preferably 2000 parts by weight or less, and more preferably 1500 parts by weight or less.
[0207] Relative to 100 parts by weight of the low molecular weight (meth)acrylic resin (C) described above, the content of the above-mentioned organic solvent in the (meth)acrylic resin composition of the present invention is preferably 25 parts by weight or more, more preferably 1,000 parts by weight or more, preferably 1,500,000 parts by weight or less, and more preferably 1,000,000 parts by weight or less.
[0208] The boiling point of the aforementioned organic solvent is preferably 90–160°C. By setting the boiling point above 90°C, premature evaporation is prevented, resulting in excellent processability. By setting the boiling point below 160°C, the strength of the inorganic microparticle dispersion can be improved.
[0209] The method for preparing the (meth)acrylic resin composition of the present invention is not particularly limited. For example, a method of mixing a (meth)acrylic resin comprising at least one of the above-mentioned high molecular weight (meth)acrylic resin (A), the above-mentioned high molecular weight (meth)acrylic resin (B), and the above-mentioned high molecular weight (meth)acrylic resin (C), the above-mentioned organic solvent, and other additives added as needed.
[0210] The (meth)acrylic resin composition of the present invention exhibits excellent low-temperature decomposition properties and excellent dispersibility and agglomeration inhibition effects of inorganic microparticles. Therefore, inorganic microparticles and plasticizers can be combined and appropriately used as inorganic microparticle dispersion slurry compositions.
[0211] Inorganic microparticle dispersion slurry compositions containing the (meth)acrylic resin composition of the present invention, inorganic microparticles, and plasticizers are also part of the present invention.
[0212] <Inorganic Particles>
[0213] The inorganic microparticle dispersion slurry composition of the present invention contains inorganic microparticles.
[0214] The aforementioned inorganic particles are not specifically limited, and examples include: glass powder, ceramic powder, phosphor particles, silicon oxides, and metal particles.
[0215] The glass powders mentioned above are not particularly limited. Examples include: bismuth oxide glass, silicate glass, lead glass, zinc glass, borosilicate glass, and various silicon oxide glass powders such as CaO-Al2O3-SiO2 system, MgO-Al2O3-SiO2 system, and LiO2-Al2O3-SiO2 system.
[0216] Alternatively, the following mixtures can also be used as the aforementioned glass powder: SnO-B2O3-P2O5-Al2O3 mixture, PbO-B2O3-SiO2 mixture, BaO-ZnO-B2O3-SiO2 mixture, ZnO-Bi2O3-B2O3-SiO2 mixture, Bi2O3-B2O3-BaO-CuO mixture, Bi2O3-ZnO-B2O3-Al2O3-SrO mixture, ZnO-Bi2O3-B2O3 mixture, Bi2O3-SiO2 mixture, P2O5-Na2O-CaO-BaO-Al2O3-B2O3 mixture, P2O5-SnO mixture, and P2O5-SnO-B2O3 mixture. Glass powders including P2O5-SnO-SiO2 mixtures, CuO-P2O5-RO mixtures, SiO2-B2O3-ZnO-Na2O-Li2O-NaF-V2O5 mixtures, P2O5-ZnO-SnO-R2O-RO mixtures, B2O3-SiO2-ZnO mixtures, B2O3-SiO2-Al2O3-ZrO2 mixtures, SiO2-B2O3-ZnO-R2O-RO mixtures, SiO2-B2O3-Al2O3-RO-R2O mixtures, SrO-ZnO-P2O5 mixtures, SrO-ZnO-P2O5 mixtures, and BaO-ZnO-B2O3-SiO2 mixtures. It should be noted that R is an element selected from Zn, Ba, Ca, Mg, Sr, Sn, Ni, Fe, and Mn.
[0217] Lead-free glass powders, such as PbO-B2O3-SiO2 mixtures, lead-free BaO-ZnO-B2O3-SiO2 mixtures, or ZnO-Bi2O3-B2O3-SiO2 mixtures, are particularly preferred.
[0218] The ceramic powders mentioned above are not particularly limited. Examples include: alumina, ferrite, zircon, zircon, barium zirconate, calcium zirconate, titanium oxide, barium titanate, strontium titanate, calcium titanate, magnesium titanate, zinc titanate, lanthanum titanate, neodymium titanate, lead zirconate titanate, aluminum nitride, silicon nitride, boron nitride, boron carbide, barium stannate, calcium stannate, magnesium silicate, mullite, block talc, cordierite, forsterite, etc.
[0219] In addition, ITO, FTO, niobium oxide, vanadium oxide, tungsten oxide, strontium lanthanum manganate (Japanese: ランタンストロンチウムマンガナイト), Lanthanum strontium cobalt ferrite (Japanese: ランタンストロンチウムコバルトフェライト), yttrium-stabilized zirconia, gadolinium-doped cerium oxide, nickel oxide, lanthanum chromate, etc.
[0220] The aforementioned phosphor particles are not particularly limited. For example, blue phosphors, red phosphors, and green phosphors, which are known as phosphors used in displays, can be used as phosphor materials. For example, MgAl can be used as a blue phosphor material. 10 O 17 Eu, Y₂SiO₅: Ce series, CaWO₄: Pb series, BaMgAl 14 O 23 Eu series, BaMgAl 16 O 27 Eu series, BaMg2Al 14 O 23 Eu series, BaMg2Al 14 O 27 Substances based on Eu and ZnS:(Ag,Cd) series. For example, Y₂O₃:Eu series, Y₂SiO₅:Eu series, and Y₃Al₅O₂ can be used as red fluorescent materials. 12 Substances such as Eu-based, Zn3(PO4)2:Mn-based, YBO3:Eu-based, (Y,Gd)BO3:Eu-based, GdBO3:Eu-based, ScBO3:Eu-based, and LuBO3:Eu-based can be used as green phosphors, for example, Zn2SiO4:Mn-based and BaAl-based substances. 12 O 19 Mn series, SrAl 13 O 19 :Mn series, CaAl12 O 19 Mn series, YBO3:Tb series, BaMgAl 14 O 23 Substances of the Mn, LuBO3:Tb, GdBO3:Tb, ScBO3:Tb, and Sr6Si3O3Cl4:Eu series can also be used. Additionally, ZnO:Zn series, ZnS:(Cu,Al) series, ZnS:Ag series, Y2O2S:Eu series, ZnS:Zn series, (Y,Cd)BO3:Eu series, and BaMgAl series can also be used. 12 O 23 Substances of the Eu series.
[0221] The aforementioned metal particles are not particularly limited, and examples include powders containing iron, copper, nickel, palladium, platinum, gold, silver, aluminum, tungsten, or their alloys.
[0222] Alternatively, metals such as copper and iron, which have good adsorption properties with carboxyl, amino, and amide groups and are easily oxidized, can be preferred. These metal powders can be used alone or in combination of two or more.
[0223] In addition to metal complexes, the aforementioned metal particles can also be various types of carbon black, carbon nanotubes, etc.
[0224] The aforementioned inorganic particles preferably contain lithium or titanium. Specifically, examples include, for instance, low-melting-point glasses such as LiO2·Al2O3·SiO2-based inorganic glasses, and Li2S-M... x S y Lithium chalcogenide glasses (M = B, Si, Ge, P), lithium cobalt composite oxides such as LiCeO2, lithium manganese composite oxides such as LiMnO4, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, lithium phosphate (Li 3.5 Si 0.5 P 0.5 O4), lithium titanium phosphate (LiTi2(PO4)3), lithium titanate (Li4Ti5O) 12 ), Li 4 / 3 Ti 5 / 3O4, LiCoO2, lithium germanium phosphate (LiGe2(PO4)3), Li2-SiS glass, Li4GeS4-Li3PS4 glass, LiSiO3, LiMn2O4, Li2S-P2S5 glass and ceramics, Li2O-SiO2, Li2O-V2O5-SiO2, LiS-SiS2-Li4SiO4 glass, LiPON ion-conducting oxides, Li2O-P2O5-B2O3, Li2O-GeO2Ba and other lithium oxide compounds, Li x Al y Tiz (PO4) 3-series glass, La x Li y TiO z Glass, Li x Ge y P z O4 series glass, Li7La3Zr2O 12 Glass, Li v Si w P x S y Cl z Lithium niobium oxides such as glass and LiNbO3, lithium alumina compounds such as Li-β-alumina, and Li 14 Zn(GeO4)4 and other lithium zinc oxides, etc.
[0225] The content of the inorganic microparticles in the inorganic microparticle dispersion slurry composition of the present invention is not particularly limited, but the preferred lower limit is 10% by weight and the preferred upper limit is 90% by weight. By setting it to 10% by weight or more, it can have sufficient viscosity and excellent coatability, and by setting it to 90% by weight or less, the dispersibility of the inorganic microparticles can be excellent.
[0226] <Other>
[0227] The inorganic particulate dispersion slurry composition of the present invention also contains a plasticizer.
[0228] Examples of plasticizers mentioned above include: di(butoxyethyl) adipate, dibutoxyethoxyethyl adipate, triethylethylene glycol dibutyl ether, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dihexanoate, triethyl acetyl citrate, tributyl acetyl citrate, diethyl acetyl citrate, dibutyl acetyl citrate, dibutyl sebacate, glyceryl triacetate, diethyl acetoxymalonate, and diethyl ethoxymalonate.
[0229] By using these plasticizers, the amount of plasticizer added can be reduced compared to the use of conventional plasticizers (it can be reduced to less than 25% by weight relative to about 30% by weight of adhesive, and further reduced to less than 20% by weight).
[0230] Preferably, non-aromatic plasticizers that do not contain aromatic rings such as benzene rings in their structure are used; more preferably, they contain components derived from bisaccharide, triethylene glycol, citric acid, or succinic acid. It should be noted that plasticizers containing aromatic rings tend to produce soot when burned, and are therefore not preferred.
[0231] Furthermore, the plasticizers described above are preferably plasticizers having alkyl groups with 2 or more carbon atoms, such as ethyl or butyl, and more preferably plasticizers having alkyl groups with 4 or more carbon atoms.
[0232] Regarding the aforementioned plasticizer, by containing an alkyl group having two or more carbon atoms, it is possible to inhibit the absorption of moisture by the plasticizer, preventing voids, bulging, and other defects in the resulting inorganic particulate dispersion. It is particularly preferred that the alkyl group in the plasticizer is located at the end of the molecule.
[0233] Furthermore, the aforementioned plasticizer preferably has functional groups with two carbon atoms, such as ethyl, functional groups with four carbon atoms, such as butyl, and functional groups such as butoxyethyl. These functional groups are preferably present in the terminal molecular chain.
[0234] Plasticizers with two-carbon functional groups, such as ethyl groups, in the terminal molecular chain exhibit good compatibility with segments derived from ethyl methacrylate, while plasticizers with four-carbon functional groups, such as butyl groups, in the terminal molecule exhibit good compatibility with segments derived from butyl methacrylate. Plasticizers with two or four carbon functional groups exhibit good compatibility with the high molecular weight (meth)acrylic resins of the present invention, and can preferably improve the brittleness of the resin. Furthermore, butoxyethyl groups exhibit good compatibility with both segments derived from ethyl methacrylate and segments derived from butyl methacrylate, and are therefore preferred for use.
[0235] The preferred carbon:oxygen ratio of the above plasticizer is 5:1 to 3:1.
[0236] By maintaining the carbon-to-oxygen ratio within the aforementioned range, the flammability of the plasticizer can be improved, preventing the formation of residual carbon. Furthermore, it enhances compatibility with (meth)acrylic resins, allowing even small amounts of plasticizer to exert their plasticizing effect.
[0237] In addition, high-boiling-point organic solvents with propylene glycol skeleton or trimethylene glycol skeleton can be preferred as long as they contain alkyl groups with 4 or more carbon atoms and the carbon:oxygen ratio is 5:1 to 3:1.
[0238] The boiling point of the aforementioned plasticizer is preferably 240°C or higher and less than 390°C. By setting the boiling point to 240°C or higher, it evaporates easily during the drying process, preventing residues from remaining in the molded article. Furthermore, by setting it to less than 390°C, residual carbon is prevented. It should be noted that the aforementioned boiling point refers to the boiling point under normal atmospheric pressure.
[0239] The content of the plasticizer in the inorganic particulate dispersion slurry composition of the present invention is not particularly limited, but the preferred lower limit is 0.1% by weight and the preferred upper limit is 3.0% by weight. By setting it within the above range, the calcination residue of the plasticizer can be reduced.
[0240] The content of the above-mentioned (meth)acrylic resin composition in the inorganic microparticle dispersion slurry composition of the present invention is not particularly limited, but the preferred lower limit is 0.5% by weight and the preferred upper limit is 10% by weight.
[0241] By setting the parameters within the above range, degreasing can be achieved even when firing at low temperatures. Furthermore, it is possible to produce an inorganic microparticle dispersion slurry composition with excellent dispersibility and agglomeration inhibition effect of inorganic microparticles.
[0242] The preferred lower limit of the content of the above (meth)acrylic resin composition is 1% by weight, and the preferred upper limit is 7% by weight.
[0243] The inorganic particulate dispersion slurry composition of the present invention may also contain additives such as surfactants.
[0244] The surfactants mentioned above are not specifically limited; for example, cationic surfactants, anionic surfactants, and nonionic surfactants can be cited.
[0245] The aforementioned nonionic surfactants are not particularly limited, but are preferably nonionic surfactants with an HLB value of 10 or higher and 20 or lower. Here, the HLB value is used as an indicator of the hydrophilicity and lipophilicity of a surfactant, and several calculation methods have been proposed, such as the following definition: for ester-based surfactants, the saponification value is set as S, the acid value of the fatty acid constituting the surfactant is set as A, and the HLB value is set as 20 (1-S / A). Specifically, nonionic surfactants having alkylene ethers added to the aliphatic chain are preferred; for example, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, etc., are preferred. It should be noted that while the aforementioned nonionic surfactants have good thermal decomposition properties, if added in large quantities, the thermal decomposition properties of the inorganic particulate dispersion slurry composition may decrease; therefore, the preferred upper limit for the content is 5% by weight.
[0246] The viscosity of the inorganic particulate dispersion slurry composition of the present invention is not particularly limited. When the viscosity is measured at 20°C using a type B viscometer with the probe rotation speed set to 5 rpm, the preferred lower limit is 0.1 Pa·s and the preferred upper limit is 100 Pa·s.
[0247] By setting the viscosity to 0.1 Pa·s or higher, the resulting inorganic microparticle dispersion can maintain a specified shape after coating using methods such as die-coating. Furthermore, by setting the viscosity to 100 Pa·s or lower, defects such as persistent die marks can be prevented, resulting in excellent printability.
[0248] The method for preparing the inorganic particulate dispersion slurry composition of the present invention is not particularly limited, and existing known stirring methods can be cited as examples. Specifically, for example, a method in which the above-mentioned (meth)acrylic resin composition, the above-mentioned inorganic particles, the above-mentioned organic solvent, and other components such as plasticizers added as needed are stirred using a three-roll mill or the like. The order in which the constituent components of the above-mentioned inorganic particulate dispersion slurry composition are added can be appropriately set.
[0249] By applying the inorganic microparticle dispersion slurry composition of the present invention onto a support film subjected to a one-sided demolding treatment, drying the organic solvent, and molding, an inorganic microparticle dispersion molded article can be manufactured. Such an inorganic microparticle dispersion molded article is also one aspect of the present invention.
[0250] The shape of the inorganic microparticle dispersion molded article of the present invention is not particularly limited, for example, it can be made into the shape of a sheet.
[0251] Examples of methods for manufacturing the inorganic microparticle dispersion of the present invention include: a method of uniformly forming a coating film on a support film using a coating method such as a roller coater, a die coater, an extrusion coater, or a curtain coater.
[0252] It should be noted that, in the case of manufacturing inorganic microparticle dispersions, it is preferable to use the polymer liquid directly as the inorganic microparticle dispersion slurry composition, so as to process the high molecular weight (meth)acrylic resin into inorganic microparticle dispersions without drying.
[0253] This is because if the high molecular weight (meth)acrylic resin is dried, undried particles called granules will be produced when it is liquefied again. These particles are difficult to remove even by using a filter cartridge or similar filter, which has an adverse effect on the strength of the inorganic particulate dispersion.
[0254] For example, when the inorganic microparticle dispersion of the present invention is in sheet form, the support film used in manufacturing the inorganic microparticle dispersion of the present invention is preferably a resin film that is heat-resistant, solvent-resistant, and flexible. By making the support film flexible, the inorganic microparticle dispersion slurry composition can be coated onto the surface of the support film by a roller coater, a doctor blade coater, or the like, and the resulting inorganic microparticle dispersion sheet can be stored and supplied in a rolled state.
[0255] Examples of resins that form the aforementioned support film include: polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, polyvinyl chloride, polyfluorinated resins such as fluorinated resins, nylon, cellulose, etc.
[0256] The thickness of the aforementioned support film is preferably 20 to 100 μm, for example.
[0257] In addition, it is preferable to perform a demolding treatment on the surface of the support film, so that the support film can be easily peeled off during the transfer process.
[0258] Inorganic microparticle dispersion slurry composition of the present invention can be coated and dried to produce inorganic microparticle dispersion molded articles.
[0259] Furthermore, multilayer ceramic capacitors can be manufactured by using the inorganic microparticle dispersion slurry composition and inorganic microparticle dispersion molded article of the present invention in dielectric green sheets and electrode pastes. Additionally, magnetic materials can be manufactured by using the inorganic microparticle dispersion slurry composition and inorganic microparticle dispersion molded article of the present invention.
[0260] As a method for manufacturing the above-mentioned multilayer ceramic capacitor, an example is a manufacturing method that includes a step of producing a dielectric sheet by printing conductive paste onto an inorganic microparticle dispersion molded article of the present invention and drying it, and a step of stacking the above-mentioned dielectric sheet.
[0261] The aforementioned conductive paste contains conductive powder.
[0262] The materials used for the aforementioned conductive powders are not particularly limited as long as they are conductive. Examples include nickel, palladium, platinum, gold, silver, copper, molybdenum, tin, and their alloys. These conductive powders can be used individually or in combination of two or more.
[0263] There are no particular limitations on the printing method for the above conductive paste. Examples include screen printing, die-coating printing, offset printing, gravure printing, and inkjet printing.
[0264] In the above-described method for manufacturing a multilayer ceramic capacitor, a multilayer ceramic capacitor is obtained by stacking dielectric sheets printed with the conductive paste.
[0265] Invention Effects
[0266] According to the present invention, a (meth)acrylic resin composition exhibiting excellent decomposability at low temperatures and capable of improving the dispersibility and agglomeration inhibition effect of inorganic particles can be provided. Additionally, inorganic particle dispersion slurry compositions and inorganic particle dispersion molded articles using the (meth)acrylic resin composition can be provided. Detailed Implementation
[0267] The following examples illustrate the present invention in more detail, but the present invention is not limited to these examples.
[0268] (Manufacturing Examples 1-28: Production of High Molecular Weight (Meth) Acrylic Resins)
[0269] Prepare a 2L separable flask equipped with a stirrer, cooler, thermometer, hot water bath, and nitrogen inlet. In the 2L separable flask, add a total of 100 parts by weight of monomers in the manner shown in Table 1. Further, mix in 50 parts by weight of butyl acetate as an organic solvent to obtain a monomer mixture.
[0270] It should be noted that the following monomers are used as monomers.
[0271] MMA: Methyl methacrylate
[0272] EMA: Ethyl methacrylate
[0273] nBMA: n-Butyl methacrylate
[0274] iBMA: Isobutyl methacrylate
[0275] 2EHMA: 2-Ethylhexyl methacrylate
[0276] HEMA: 2-Hydroxyethyl methacrylate
[0277] HPMA: 2-Hydroxypropyl Methacrylate
[0278] HBMA: 2-Hydroxybutyl Methacrylate
[0279] The obtained monomer mixture was bubbled with nitrogen for 20 minutes to remove dissolved oxygen. The system was then purged with nitrogen in a separable flask while stirring and heating to boiling in a hot water bath. The polymerization initiator and chain transfer agent were added in the amounts shown in Table 1.
[0280] Seven hours after the start of polymerization, the mixture was cooled to room temperature to end the polymerization. Then, the resulting resin solution was dried in an oven at 130°C to remove the organic solvent. This yielded a high molecular weight (meth)acrylic resin.
[0281] It should be noted that the following substances are used as polymerization initiators and chain transfer agents.
[0282] <Polymerization Initiator>
[0283] tert-butyl peroxypentanoate
[0284] <Chain transfer agent>
[0285] CT-1: 3-Mercapto-1,2-Propanediol
[0286] CT-2: 3-Mercapto-1-propanol
[0287] CT-3: 3-Mercapto-2-butanol
[0288] CT-4: 8-Mercapto-1-Octanol
[0289] CT-5: Thiosulfonic acid
[0290] [Table 1]
[0291]
[0292] (Manufacturing Examples 29-62: Production of Low Molecular Weight (Meth)Acrylic Resins and Other (Meth)Acrylic Resins)
[0293] Prepare a 2L separable flask equipped with a stirrer, cooler, thermometer, hot water bath, and nitrogen inlet. In the 2L separable flask, add a total of 100 parts by weight of monomers in the manner shown in Table 2. Further mix with 50 parts by weight of butyl acetate as an organic solvent to obtain a monomer mixture.
[0294] It should be noted that the same monomers as those used in manufacturing examples 1 to 28 are used.
[0295] The obtained monomer mixture was bubbled with nitrogen for 20 minutes to remove dissolved oxygen. The system was then purged with nitrogen in a separable flask while stirring and heating to boiling in a hot water bath. Polymer initiators and chain transfer agents were added in the types and amounts shown in Table 2.
[0296] Seven hours after the start of polymerization, the mixture was cooled to room temperature to end the polymerization. The resulting resin solution was then dried in an oven at 130°C to remove the organic solvent. This yielded a low molecular weight (meth)acrylic resin.
[0297] It should be noted that the same polymerization initiator and chain transfer agent as those used in manufacturing examples 1 to 28 are used.
[0298] [Table 2]
[0299]
[0300] (Examples 1-29, Comparative Examples 1-8)
[0301] (1) Preparation of resin composition
[0302] Organic solvents were mixed in a manner as shown in Table 4 to obtain a mixed solvent. (Meth)acrylic resin and the mixed solvent were mixed in a manner as shown in Table 3 to obtain a (meth)acrylic resin composition.
[0303] It should be noted that the following organic solvents are used as organic solvents.
[0304] Toluene
[0305] Ethyl acetate
[0306] Methyl ethyl ketone
[0307] ethanol
[0308] Isopropanol
[0309] 2-Butyl-2-ethyl-1,3-propanediol (BEPG)
[0310] Neopentyl glycol (NPG)
[0311] TEXANOL
[0312] (2) Preparation of inorganic microparticle dispersion slurry composition
[0313] Ceramic powder and plasticizer were added to the obtained (meth)acrylic resin composition in the manner described in Table 3, and the mixture was kneaded using a high-speed mixer to prepare an inorganic particulate dispersion slurry composition.
[0314] It should be noted that the copper powder (manufactured by Fujino Metal Co., Ltd., with an average particle size of 0.1 μm) and the glass powder (manufactured by AGC Co., Ltd., with an average particle size of 0.8 μm) used as ceramic powders, and di(butoxyethyl) adipate was used as a plasticizer.
[0315] <Evaluation>
[0316] The high molecular weight (meth)acrylic resin, low molecular weight (meth)acrylic resin, and inorganic particulate dispersion slurry compositions obtained in the Examples and Comparative Examples were evaluated as follows. The results are shown in Tables 1 to 3.
[0317] (1) Determination of weight-average molecular weight
[0318] For the obtained high molecular weight (meth)acrylic resins and low molecular weight (meth)acrylic resins, the weight-average molecular weight (Mw) based on polystyrene was determined by gel permeation chromatography using an LF-804 column (manufactured by SHOKO).
[0319] (2) Calculation of the weight concentration of OH groups
[0320] The weight concentration of OH groups in high molecular weight (meth)acrylic resins, low molecular weight (meth)acrylic resins, and organic solvents was calculated using the following methods.
[0321] The weight concentration of OH groups in high molecular weight (meth)acrylic acid resins: [Weight of OH groups in all monomers / (Weight of all monomers + Weight of polymerization initiator)] × 100
[0322] The weight concentration of OH groups in low molecular weight (meth)acrylic resins: [(Weight of OH groups in all monomers + Weight of OH groups in chain transfer agent) / (Weight of all monomers + Weight of chain transfer agent + Weight of polymerization initiator)] × 100
[0323] Weight concentration of OH groups in an organic solvent: (Weight of OH groups in all organic solvents / Weight of all organic solvents) × 100
[0324] (3) Calculation of the weight concentration of S atoms
[0325] The weight concentration of sulfur atoms in (meth)acrylic resins was calculated using the following method.
[0326] The weight concentration of sulfur atoms in (meth)acrylic resins = [weight of sulfur atoms in the chain transfer agent / (weight of all monomers + weight of polymerization initiator + weight of chain transfer agent)] × 100
[0327] It should be noted that when the above-mentioned (meth)acrylic resin composition contains multiple (meth)acrylic resins, the weight concentration of S atoms is calculated based on the weight concentration of S atoms contained in each (meth)acrylic resin and the proportion of each (meth)acrylic resin.
[0328] (4) Determination of solubility in ethanol
[0329] At 25°C, the high molecular weight (meth)acrylic resin was dissolved in small amounts each time relative to 100 parts by weight of ethanol, and the amount of high molecular weight (meth)acrylic resin required to produce precipitates was taken as the solubility in ethanol.
[0330] (5) Low-temperature decomposition property (TGDTA characteristic)
[0331] The obtained inorganic particulate dispersion slurry composition was filled into a platinum dish of TG-DTA, and the temperature was increased from 30°C to 5°C / min to evaporate the solvent and thermally decompose the resin and plasticizer. Then, the time to reach 52.1% by weight (90% degreasing completed) was measured.
[0332] (6) Filterability
[0333] A syringe containing 2 ml to 2.5 ml of the obtained inorganic microparticle dispersion slurry composition was used. An injection needle with an outer diameter of 0.81 mm, an inner diameter of 0.51 mm, and a length of 38 mm was installed at the tip of the syringe. The time it took for the slurry composition to be completely extracted from the tip of the injection needle when a force of 5 kgf was applied was measured.
[0334] If the time from when the slurry composition is completely discharged from the tip of the injection needle is short, it can be considered to have excellent filtration performance. In the case of excellent filtration performance, it can be considered to have a high inhibition effect on the aggregation of inorganic particles.
[0335] (7) Surface roughness
[0336] Using a screen printing machine and a screen printing plate, an inorganic microparticle dispersion paste composition was printed onto a glass substrate at a temperature of 23°C and a humidity of 50%. The mixture was then solvent-dried in a blower oven at 100°C for 30 minutes. The resulting printed pattern was then measured at 10 locations using a surface roughness meter (Surfcom, Tokyo Seimitsu Co., Ltd.).
[0337] It should be noted that the following products are used as screen printing machines, screen printing plates, and printing glass substrates.
[0338] Screen printing machine (MT-320TV, manufactured by Micro Tech)
[0339] Screen printing plate (made by Tokyo Process Service, ST500, 2μm emulsion, 2012 pattern, screen frame 320mm×320mm)
[0340] Printed glass substrate (sodium glass, 150mm × 150mm, 1.5mm thickness)
[0341] If the surface roughness is small, it can be considered that the inorganic particles have excellent dispersibility.
[0342] (8) Ethanol cleaning properties
[0343] Add 100 parts by weight of ethanol to 10 parts by weight of the inorganic particulate dispersion slurry composition, and irradiate with ultrasound. Measure the time required for the resin to completely dissolve in the ethanol.
[0344] [Table 3]
[0345]
[0346] [Table 4]
[0347]
[0348] Industrial availability
[0349] According to the present invention, a (meth)acrylic resin composition exhibiting excellent decomposability at low temperatures and capable of improving the dispersibility and agglomeration inhibition effect of inorganic particles can be provided. Additionally, inorganic particle dispersion slurry compositions and inorganic particle dispersion molded articles using the (meth)acrylic resin composition can be provided.
Claims
1. A (meth)acrylic resin composition comprising a (meth)acrylic resin and an organic solvent, The organic solvent contains organic solvents with OH groups. The (meth)acrylic resin composition satisfies any one of the following (1) to (3), The organic solvent contains OH groups at a weight concentration of 9.0% by weight or more and 28.0% by weight or less. (1) The (meth)acrylic resin contains a high molecular weight (meth)acrylic resin A with a weight-average molecular weight of 120,000 or more and 300,000 or less. The high molecular weight (meth)acrylate resin A contains segments of (meth)acrylates of formula (b) shown below, derived from straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group, and segments of (meth)acrylates of formula (a) shown below, derived from straight-chain or branched alkyl groups. The high molecular weight (meth)acrylic acid resin A contains OH groups at a weight concentration of 0.4% to 2.0% (wt%). The solubility of the high molecular weight (meth)acrylic resin A in ethanol is more than 10 parts by weight per 100 parts by weight of ethanol. (2) The (meth)acrylic resin contains a high molecular weight (meth)acrylic resin B with a weight-average molecular weight exceeding 300,000 and below 500,000. The high molecular weight (meth)acrylate resin B contains segments of (meth)acrylates of formula (b) shown below, derived from straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group, and segments of (meth)acrylates of formula (a) shown below, derived from straight-chain or branched alkyl groups. The weight concentration of OH groups in the high molecular weight (meth)acrylic acid resin B is 1.3% by weight or more and 3.5% by weight or less. The high molecular weight (meth)acrylic acid resin B has a solubility of more than 10 parts by weight in ethanol per 100 parts by weight of ethanol. In equation (a), R 1 In formula (b), R represents a straight-chain or branched alkyl group having 1 to 8 carbon atoms. 2 A straight-chain or branched alkyl group comprising 2 to 4 carbon atoms, in which at least one hydrogen atom is replaced by an OH group. (3) The (meth)acrylic resin contains low molecular weight (meth)acrylic resin C with a weight-average molecular weight of 0.5 million or more and 100,000 or less. The (meth)acrylic resin C contains segments of (meth)acrylates comprising 2-4 straight-chain or branched alkyl groups having at least one hydrogen atom substituted with an OH group, and segments of (meth)acrylates comprising 3-4 straight-chain or branched alkyl groups having 3-4 carbon atoms. The weight concentration of OH groups in the low molecular weight (meth)acrylic resin C is 1.3% by weight or more and 3.5% by weight or less. The (meth)acrylic resin contains a sulfur atom concentration of 250 ppm or more and 20,000 ppm or less by weight. The S atom comes from the chain transfer agent.
2. The (meth)acrylic resin composition according to claim 1, which satisfies (1) and contains a low molecular weight (meth)acrylic resin with a weight average molecular weight of 0.5 million or more and 100,000 or less, wherein the weight concentration of OH groups contained in the low molecular weight (meth)acrylic resin is 1.3% by weight or more and 3.5% by weight or less, and the content of the low molecular weight (meth)acrylic resin is 0.1 parts by weight or more and 10 parts by weight or less relative to 100 parts by weight of high molecular weight (meth)acrylic resin A100.
3. The (meth)acrylic resin composition according to claim 1, wherein it satisfies (1) or (2).
4. The (meth)acrylic resin composition according to claim 1 or 3, which satisfies (1) or (2), and the high molecular weight (meth)acrylic resin A or high molecular weight (meth)acrylic resin B contains, relative to all structural units, 79% by weight or more and 96% by weight of structural units represented by formula (a) and 3.1% by weight or more and 17% by weight of structural units represented by formula (b). In equation (a), R 1 In formula (b), R represents a straight-chain or branched alkyl group having 1 to 8 carbon atoms. 2 It refers to a straight-chain or branched alkyl group in which at least one of the hydrogen atoms is replaced by an OH group, and the number of carbon atoms is 2 to 4.
5. The (meth)acrylic resin composition according to claim 1 or 3, which satisfies (1) or (2), and the weight concentration of OH groups contained in the organic solvent relative to the weight concentration of OH groups contained in high molecular weight (meth)acrylic resin A or high molecular weight (meth)acrylic resin B, i.e., the weight concentration of OH groups contained in the organic solvent / the weight concentration of OH groups contained in high molecular weight (meth)acrylic resin A or high molecular weight (meth)acrylic resin B, is 4.5 or more and 46.2 or less.
6. The (meth)acrylic resin composition according to claim 1 or 3, wherein it satisfies (2), and the (meth)acrylic resin is composed solely of high molecular weight (meth)acrylic resin B. The weight concentration of sulfur atoms in the (meth)acrylic resin is above 250 ppm and below 20,000 ppm.
7. An inorganic particulate dispersion slurry composition comprising the (meth)acrylic resin composition according to any one of claims 1 to 6, inorganic particulates, and a plasticizer.
8. An inorganic microparticle dispersion molding article, which is formed using the inorganic microparticle dispersion slurry composition of claim 7.
Citation Information
Patent Citations
Methods for producing ceramic slurry, green sheet and electronic component
JP2011084433A
Conductive paste and method for forming conductor film
JP2020109761A
Use of statistical copolymers
JP2008510602A